PENGARUH LITERASI KEUANGAN DAN LITERASI E-COMMERCE TERHADAP KINERJA UMKM BIDANG KULINER DI DESA SUKAHARJA KECAMATAN TELUKJAMBE TIMUR KABUPATEN KARAWANG - Zaidan Al Rahman; Danang Kusnanto (Institut Teknologi dan Bisnis Dewantara, 2025)
The research method used in this study is a descriptive verification method with a quantitative approach. The sampling technique uses probability sampling with a proportionate stratified random sampling type, obtaining a sample of 127 respondents who are MSMEs. Then the analysis used in this study is path analysis. The results of the study show that the picture for financial literacy, e-commerce literacy, and performance of culinary MSMEs in Sukaharja Village is considered good. The correlation between Financial Literacy and E-Commerce Literacy has a strong relationship of 0.874. There is a partial influence of Financial Literacy on Business Performance of 31.89%. There is a partial influence of E-Commerce Literacy on Business Performance of 59.12%. There is a simultaneous influence of Financial Literacy and E-Commerce Literacy on Business Performance of Culinary MSMEs in Sukaharja Village of 91.01% while the remaining 8.99% is influenced by other variables not examined in this study.